TRANSPARANSI MUTASI PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN HALMAHERA UTARA - TAWARIS, MARIO; kALANGI, JHONNY; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2018)
This study moved from the initial observation that the process of implementation anddetermination of mutations of civil servants in the local government of North Halmahera Regency is lesstransparent. Thus, the research in addition to answering the problems related to transparency of civilservant mutations, also aims to know the application of the principle of transparency in the implementationof employee mutations at the Regional Personnel Agency (BKD) of North Halmahera Regency. Thisresearch applies descriptive method with qualitative approach, informant is determined based on level ofunderstanding to research problem as many as 12 people consisting of element BKD, some related SKPD,Member DPRD related commission and press. Methods of data collection consist of observation,documentation and interview. Processing and data analysis is done from the collection stage to the dataverifikasi stage by applying interactive techniques.The results showed that (1). Information relating to the process of formulating and implementing publicpolicies, including information on civil servant mutations, is sufficient, accessible, accessible and timely,but information is categorized as